An Overview of 1,2,3-triazole-Containing Hybrids and Their Potential Anticholinesterase Activities - Shah Alam Khan; Mohammad Jawaid Akhtar; Urvashee Gogoi; Dhanalekshmi Unnikrishnan Meenakshi; Aparoop Das (MDPI AG, 2023)
Acetylcholine (ACh) neurotransmitter of the cholinergic system in the brain is involved in learning, memory, stress responses, and cognitive functioning. It is hydrolyzed into choline and acetic acid by two key cholinesterase enzymes, viz., acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). A loss or degeneration of cholinergic neurons that leads to a reduction in ACh levels is considered a significant contributing factor in the development of neurodegenerative diseases (NDs) such as Alzheimer's disease (AD). Numerous studies have shown that cholinesterase inhibitors can raise the level of ACh and, therefore, enhance people's quality of life, and, at the very least, it can temporarily lessen the symptoms of NDs. 1,2,3-triazole, a five-membered heterocyclic ring, is a privileged moiety, that is, a central scaffold, and is capable of interacting with a variety of receptors and enzymes to exhibit a broad range of important biological activities. Recently, it has been clubbed with other pharmacophoric fragments/molecules in hope of obtaining potent and selective AChE and/or BuChE inhibitors. The present updated review succinctly summarizes the different synthetic strategies used to synthesize the 1,2,3-triazole moiety. It also highlights the anticholinesterase potential of various 1,2,3-triazole di/trihybrids reported in the past seven years (2015-2022), including a rationale for hybridization and with an emphasis on their structural features for the development and optimization of cholinesterase inhibitors to treat NDs.